A PROGRAM AND ANALYZE OF SYSTEM CIVIL PERPEFTIF IN TERMS OF COPYRIGHT AND PATENT DIGITAL - Winta Hayati; Khomaini Khomaini (Jurnal Info Sains : Informatika dan Sains, 2023)
This paper discussed about a legal aspects of transferring copyright for book works in Indonesia, particularly from the perspective of Civil Inheritance Law. It highlights that while the Copyright Law (Law Number 28 of 2014) doesn't provide detailed procedures for transferring copyrights through inheritance, it can be done after the author's or copyright holder's death, with the inheritance automatically passing to the heirs. It also mentions that book copyrights can be inherited in the form of licenses or royalties, which are regulated under the UUHC (presumably a relevant law).the article recommends that the government should provide public education and counseling on copyright, especially for book works. Authors are encouraged to transfer their creations through an application for registration with the Directorate General of Intellectual Property (Dirjen KI) in Jakarta or through the Regional Offices of the Ministry of Law and Human Rights in different regions.